The effectiveness of acceptance and commitment group therapy on cognitive fusion and health locus of control in patients with type 2 diabetes - Fariba Lotfi; Asghar Nakhostin Goldoost; Tavakol Mousazadeh; Reza Kazemi (فصلنامه ابن سینا)
Background and Aims: Diabetes can have significant psychological effects on health. Therefore, the aim of this study was to determine the effectiveness of group therapy based on acceptance and commitment on cognitive fusion and health locus of control of type 2 diabetic patients. Methods: The present study was a quasi-experimental design of pre-test, post-test and follow-up with a control group. From the statistical population of the study, which included all patients with type 2 diabetes referred to diabetes Clinic of Dey Hospital in Tehran in the second six months of 2020, a sample of 30 people were randomly selected and randomly divided into experimental and control groups. Initially, cognitive fusion questionnaires and health control centers were administered in both groups. The experimental group then underwent 8 sessions of 90-minute group therapy based on acceptance and commitment of Hayes et al. but the control group did not receive any treatment. Data were analyzed using SPSS software version 24 and analysis of variance with repeated measures between groups at the significance level of α = 0.05. Findings: The results showed that acceptance and commitment to group therapy led to a reduction in cognitive fusion and improved health Locus of control for type 2 diabetic patients (P <0.05). Conclusion: Acceptance and commitment group therapy can help improve the psychological symptoms of diabetic patients and reduce the psychological consequences of diabetes.